Pemberdayaan Ibu-ibu PKK Nagari Sikucur Barat Melalui Produksi Virgin Coconut Oil (VCO) - Femi Earnestly (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2019)
Women from Sikucur Barat are economically unproductive because they generally can’t support their family income. Sikucur Barat produces many coconuts and is supposed to become a chance for the women to have side income and women who belong to PKK’s group. In fact the family can’t rely on their life from coconut since the price is getting low only Rp.1.000. It makes the people let the coconut fall down on the ground without collecting them. This condition happens because they are unable to cover the transportation fee if sold to other cities such as Padang or Pekanbaru. Besides, the people don’t have knowledge on how to process the coconut becomes the highest quality product such as Virgin Coconut Oil (VCO). Based on this problem, we try to do PKM (Service for Society) by giving training how to make right VCO, branding it, and Depkes (Health Department) permit for PKK’s women in Sikucur Barat village. Thus, we hope it can become a new entrepreneur to support their income and increase the knowledge and the skills of the society of PKK’s group in Sikucur Barat village. We spread the questionnaires and got the result that about 89,4% of the society’s income increased